Spontaneous rupture of an intraorbital hydatid cyst: A rare cause of acute visual loss - (:unkn) unknown (My University, 1993)
A very rare cause of acute visual loss due to the spontaneous rupture of an intraorbital hydatid cyst is presented. Acute onset was thought to be due to volume expansion and inflammatory reaction of orbital structures to ruptured cyst fluid. © 1993 Raven Press, Ltd., New York.
Keywords: Echinococcosis; Hydatid cyst; MRI; Orbita; Orbital hydatid-Proptosis